UHF-RFID technology for smart tire presence detection: Performance evaluation and IoT integration - Rahman, Mahfud Rozaki; Mutiara, Giva Andriana; Alfarisi, Muhammad Rizqy (Review of Computer Engineering Research, 2025)
This study aims to develop a smart tire presence detection system using UHF-RFID technology and the ESP32 microcontroller to prevent vehicle tire theft and unauthorized replacement. A prototype-based methodology was used, employing iterative testing and development cycles. Two UHF RFID readers—EL-UHF-RF014 and BR-20—were compared to determine optimal performance in detection range and response time. The selected reader was integrated into a system that transmits real-time data to an IoT-based web interface. The EL-UHF-RF014 outperformed the BR-20 in all scenarios, achieving a maximum detection range of 12 meters and faster response times. Real-time monitoring results showed a detection accuracy of 87.5%. The best antenna position for consistent detection was on the side of the vehicle, with average response times of 1.4 seconds. The proposed system reliably detects tire presence and improves vehicle safety. The EL-UHF-RF014 reader, combined with tire-integrated RFID tags and IoT connectivity, enables effective monitoring of tire conditions and prevents unnoticed tire swaps. The system is applicable in automotive workshops and fleet management, improving security and operational efficiency. It serves as a foundation for future IoT-based vehicle safety innovations.